2005
DOI: 10.1074/jbc.m507042200
|View full text |Cite
|
Sign up to set email alerts
|

Basis for Selectivity of Cationic Antimicrobial Peptides for Bacterial Versus Mammalian Membranes

Abstract: Novel cationic antimicrobial peptides typified by structures such as KKKKKKAAXAAWAAXAA-NH 2 , where X ‫؍‬ Phe/Trp, and several of their analogues display high activity against a variety of bacteria but exhibit no hemolytic activity even at high dose levels in mammalian erythrocytes. To elucidate their mechanism of action and source of selectivity for bacterial membranes, phospholipid mixtures mimicking the compositions of natural bacterial membranes (containing anionic lipids) and mammalian membranes (containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
239
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(259 citation statements)
references
References 56 publications
(51 reference statements)
12
239
0
4
Order By: Relevance
“…20 In the present work, all 2-, 3-, and Leu isomeric peptides migrate on SDS-PAGE as dimers. Such dimerization must relate to the presence of highly potent helix-helix interaction motifs in their sequence.…”
Section: Designed Caps Form Dimers In Hydrophobic Environmentssupporting
confidence: 49%
See 2 more Smart Citations
“…20 In the present work, all 2-, 3-, and Leu isomeric peptides migrate on SDS-PAGE as dimers. Such dimerization must relate to the presence of highly potent helix-helix interaction motifs in their sequence.…”
Section: Designed Caps Form Dimers In Hydrophobic Environmentssupporting
confidence: 49%
“…A similar pattern was noted earlier for Lys-tagged 25-residue peptides with 19-residue core hydrophobic segments. 17 However, when this paradigm was applied to zwitterionic mammalian-like membranes, we found for similar peptides containing highly charged Lys tags attached to a core hydrophobic sequence, 20 that peptides ultimately cannot leave the bulk water for attachment/insertion into erythrocyte-like bilayers until their CSH begins to approach sufficiently high levels, as in the case where the sequence contains at least two Ala-toLeu substitutions (see Fig. 2).…”
Section: Hydrophobicity Thresholds For Membrane Insertion Of Capsmentioning
confidence: 96%
See 1 more Smart Citation
“…In designing this peptide, Ala was chosen as the background residue due to its midrange hydrophobicity and frequent occurrence in membrane domains. As well, the AxxxA ("small-xxxsmall") sequence motif promotes peptide dimerization in membranes (9,10), which has been suggested to enhance antimicrobial activity (11). The Trp residue in the hydrophobic core serves as the fluorescent probe, whereas the positively charged Lys residues were included at the terminus to maintain cationic properties and enhance peptide solubility.…”
mentioning
confidence: 99%
“…The negatively charged bacterial lipid PG behaved in a similar manner to the PS, emphasizing the importance of an electrostatic interaction with the positively charged AMP (Matsuzaki et al, 1989;Lohner and Prenner, 1999). A more accurate representation of the E. coli membrane was provided by using a headgroup ratio of 75:20:5 POPE/DPPG/CL in SUVs and LUVs (Glukhov et al, 2005) to study the differential targeting of novel cationic AMPs to bacterial versus mammalian membranes. They found that the initial attraction between the positive AMP and negatively charged bacterial membranes was an important component of bacterial/mammalian selectivity.…”
Section: Antimicrobial Peptides: Vesiclesmentioning
confidence: 99%